2014
DOI: 10.1088/1475-7516/2014/02/035
|View full text |Cite
|
Sign up to set email alerts
|

A polynomial f(R) inflation model

Abstract: Motivated by the ultraviolet complete theory of quantum gravity, for example the string theory, we investigate a polynomial f (R) inflation model in detail. We calculate the spectral index and tensorto-scalar ratio in the f (R) inflation model with the form of f (R) = R+ R 2 6M 2 + λn 2n R n (3M 2 ) n−1 . Compared to Planck 2013, we find that R n term should be exponentially suppressed, i.e. |λn| < ∼ 10 −2n+2.6 .PACS numbers:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 40 publications
3
82
0
Order By: Relevance
“…Such a formalism successfully describes both the inflationary era [7,8] and the current phase of accelerated expansion our Universe is undergoing [9,10], the latter, with no need of a CC.…”
Section: Introductionmentioning
confidence: 99%
“…Such a formalism successfully describes both the inflationary era [7,8] and the current phase of accelerated expansion our Universe is undergoing [9,10], the latter, with no need of a CC.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper we study the simplest f (R) theory, namely R + βR N . This theory has been well-investigated in the Einstein frame in the context of inflationary dynamics ( [43][44][45]). The scalaron potential in the chosen unit system (footnote 2) has the following form,…”
Section: The Model and A Picture In The Einstein Framementioning
confidence: 99%
“…Finally from (43,44,45) the Hubble parameter and the matter energy density as functions of time are given by…”
Section: First Order Solution Of the Perturbed Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the slow-roll inflation can be achieved as long as the dimensionless coupling λ n is sufficiently small [11].…”
Section: Introductionmentioning
confidence: 99%